Approximation Several Zeroes of a Class of Periodical Complex Functions (Journal of Computational Mathematics, 2021)
This paper discussed the number of zeros of the complex function $F:C → C$ defined by $$F(Z)=\sum\limits_{k=1}^n(a_k cos(kZ)+b_k sin(kZ))+α_0+α_1 Im(z)+…+α_m(Im(Z))^m.$$